Assessment of trade credit risk in business companies - Každailienė, Jūratė; Daujotaitė, Dalia (Buhalterinės apskaitos teorija ir praktika, 2014)
The article‘s topic is relevant, because the importance of trade credit constantly increases. Trade credit can be one of the most important preconditions for the competitiveness of the enterprise and business development. There is a lack of scientific sources in the field of estimation of trade credit risk – there is no any particular, simple to use methodology to assess company trade credit risk. The aim of the article – to compose a methodology of assessment company trade credit risk for Lithuanian small and medium enterprises. In the article, following scientific sources approach, the advantages, risks and key financial and non-financial trade credit risk factors were identified. Based on the scientific sources and expert evaluation, the methodology of company trade credit risk assessment was created. The methodology is based on 10 key indicators identified by the experts. 12 financial ratios and non-financial indicators are being used – current and quick ratio, gross and net profit margin, Altman Z model, debt ratio, stock and debtors turnover, enterprise age, reputation, number and dynamics of employees. The indicators have been scored. The highest possible score is 100. The research approves that the methodology suits to be used in practice. It is simple, reliable, cheap, non-time consuming; it is easy to collect data, the data is being formalized and quantified. The disadvantages of methodology – the data is not always reliable and some ratios are of different importance in the different economic sectors. The methodology should be modified to adapt for the different sectors of business.